Pelatihan Manajemen SDM Dan Peningkatan Kapasitas Karyawan Sebagai Upaya Pemberdayaan UMKM - Cep Lukman Rohmat; Dadang Sudrajat; Fatkhan Mubarok; Muhammad Agastya (CV. Multi Kreasi Media, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in national economic development, particularly in creating jobs and improving people's welfare. However, MSMEs often face various challenges in managing human resources (HR) and increasing employee capacity, which has a direct impact on productivity and business sustainability. This research aims to empower MSME actors through HR management training and employee capacity building. The method used is integrated training that includes workforce needs planning, recruitment and selection, training and development, and performance evaluation. Training activities were carried out in the form of workshops, group discussions, and hands-on practices involving the active participation of MSME actors. The results of the training showed an increase in MSME actors' understanding of the importance of HR management and positive changes in the application of management practices in their respective business environments. In addition, the training also contributes to increasing employee motivation and competence, which in turn improves business performance and competitiveness. With this empowerment program, MSMEs are expected to grow more professional, adaptive, and sustainable. This study recommends continuous assistance and support from the government and related institutions to strengthen the managerial capacity of MSME actors in the long term.